Study of Clinical, Angiographic Profile and Outcome of Patients Undergoing Coronary Angioplasty of Left main Coronary Artery: MCVTC Experience. - Gajurel, Ratna Mani; Khanal, Raja Ram; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Shakya, Smriti (Nepalese Heart Journal, 2021)
Background and Aims: Coronary artery bypass graft is the treatment of choice for left main disease. However the results from several large multicenter trials have shown that the angioplasty of left main disease is an alternative treatment. The aim of this study was to assess the outcome of patients undergoing angioplasty of left main disease. Methods: This prospective study was conducted at Manmohan cardiothoracic vascular and transplant center, Maharajgunj, Kathmandu, Nepal. Twenty-Five patients with a diagnosis of left main coronary artery disease who underwent coronary angioplasty were enrolled in the study. The cases were followed up and outcomes on follow up were assessed. Results: Patients with left main disease enrolled in this study belonged to the age group of 51 to 77 years. The mean age of patients was 64.7±8.12 with 68% (17) male and 32% (8) female. Among 25 patients 3 patients had single vessel disease, double vessel in 10 patients and triple vessel in 12 patients. Three patients (12%) had previous history of percutaneous coronary intervention and 1 (4%) had previous history of coronary artery bypass graft. All patients underwent successful procedure with unprotected left main stenting in 14 cases (56%). There was few major and minor complications and no procedure related mortality and in hospital death. Conclusion: Left main coronary angioplasty is a safe and alternative procedure to CABG with low incidence of major clinical events.